REALISASI STRATEGI KESANTUNAN POSITIF DAN KESANTUNAN NEGATIF PADA PODCAST YOUTUBE - Kevin Andrian Seda; Wawan Gunawan; R Dian Dia-an Muniroh (Jurnal Ilmiah Wahana Pendidikan, 2023)
Abstract This article aims to identify politeness strategies based on Brown and Levinson's theory in the speech of a YouTube podcast channel hosted by Denny Sumargo. The research focuses on two strategies, namely positive politeness strategy and negative politeness strategy. The approach used in this research is a qualitative descriptive approach. The data for this study consists of speech transcripts from the YouTube podcast video. The data collection technique employed in this research is note-taking. The results of this study indicate that in the podcast, positive politeness strategies are used more frequently than negative politeness strategies. This suggests that familiarity is employed to maintain harmonious relationships and avoid conflicts in communication. Keyword : negative politeness, positive politeness, podcast.